The Effect of pineaple juice (Ananas comosus) on Blood Cholesterol Level of Rabbit (Oryctolagus cuniculus) hipercholesterolemia - Zuhrawati N. A. (Jurnal Medika Veterinaria, 2014)
This study aims to know the effect of pineapple juice on blood cholesterol level of male hypercholesterolemic rabbits. A total of 12 local male rabbits aged 1-2 years with body weight ranging from 0.9-1.6 kg were used as sampel. Sample were divided randomly into 4 treatmentgroups, each group consisting of 3 replications. All rabbits were initially examined for the total cholesterol levels, before fed with a diet to makehypercholesterolemic. The rabbits were then fed with a mixture of 90% sugar solution as much as 6 gr/kg body weight and egg yolks as much as3 gr/kg body weight for 7 consecutive days using a stomach sonde, followed with re-examination of total cholesterol. Samples were thenadministered with pineapple juice on KI (10 g /kg BW), KII (20 g/kg BW), and KIII (30 g/kg), while the K0 as controls were not given pineapplejuice. After 10 days of administration of pineapple juice, rabbit blood was collected through the auricular vein for total cholesterol examinationusing the Chod-PAP. Data were analyzed by ANOVA completely randomized design (CRD) one way, and the difference between the treatmentgroup was examined using Duncan's multiple test. Results showed that the mean (±SD) of total blood cholesterol levels of rabbits (mg/dl) groupsK0, KI, KII, and KIII after the administration of pineapple juice in a row was 176.60 ± 57.10; 66.60±12.50; 63±17.70; and 57.60±24.80.Statistical analysis showed that treatment affect significantly (P0.05) to decrease total blood cholesterol levels of rabbits. In conclusion, theadministration of pineapple juice (Ananas comosus) for ten consecutive days can decrease blood total cholesterol of hypercholesterolemiarabbits.____________________________________________________________________________________________________________________Key words: diet cholesterol, pineapple juice, total cholesterol levels, rabbit